2001
DOI: 10.1530/rep.0.1220619
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of connexin 43 in meiotic maturation of bovine oocytes

Abstract: In ovarian follicles, cumulus cells provide the oocyte with small molecules that permit growth and control maturation. These nutrients reach the germinal cell through gap junction channels, which are present between the cumulus cells and the oocyte, and between the cumulus cells. In this study the involvement of intercellular communication mediated by gap junction channels on oocyte maturation of in vitro cultured bovine cumulus-oocyte complexes (COCs) was investigated. The stages of oocyte maturation were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 14 publications
5
37
0
1
Order By: Relevance
“…Although not always comparable to results achieved under less extreme conditions, there was rather striking success in these oocytes having the capacity to mature, fertilize and advance to blastocyst stages in vitro. Interestingly, exposure of cat oocytes to the excessive 2,000 mOsm treatment was not as detrimental to COC functionality as denuding all cumulus cells or artificially disrupting communications with the oocyte by other artificial means (Vozzi et al, 2001;Atef et al, 2005;Luciano et al, 2005). This shows that a minimum of communications (not detectable by Lucifer Yellow diffusion) were retained within the COC exposed to 2,000 mOsm which allowed producing viable appearing embryos.…”
Section: Discussionmentioning
confidence: 93%
“…Although not always comparable to results achieved under less extreme conditions, there was rather striking success in these oocytes having the capacity to mature, fertilize and advance to blastocyst stages in vitro. Interestingly, exposure of cat oocytes to the excessive 2,000 mOsm treatment was not as detrimental to COC functionality as denuding all cumulus cells or artificially disrupting communications with the oocyte by other artificial means (Vozzi et al, 2001;Atef et al, 2005;Luciano et al, 2005). This shows that a minimum of communications (not detectable by Lucifer Yellow diffusion) were retained within the COC exposed to 2,000 mOsm which allowed producing viable appearing embryos.…”
Section: Discussionmentioning
confidence: 93%
“…In the single-step method, as in the previous report [26] treatments of EFS30 showed that the GV-COCs after vitrification had partly dispersed cumulus cells and oocytes with shrunken cytoplasm. The connection between cumulus cells and the oocyte in the GVCOCs is shown to be important for completion of normal oocyte maturation in vitro [27]. Hochi, et al, [28] vitrified immature bovine oocytes in straws by using a mixture of 40% EG, ficoll and sucrose as a vitrification medium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results reported indicated that increased expression of Cx43 temporally correlates with the activation of follicular development and early differentiation of granulosa cells in follicles of prepubertal pig ovaries. Vozzi et al [81] indicated that in ovarian follicles, oocyte is provided by cumulus cells with small molecules that license control maturation and growth. The germinal cell gets these nutrients through gap junction channels, present between the oocyte and cumulus cells.…”
Section: The Cx43 Genementioning
confidence: 99%